Analisis Kesuksesan Layanan Digital Perguruan Tinggi Menggunakan Model Delone & McLean untuk Meningkatkan Kepuasan Pengguna - Wulansari, Anita; Kartika, Dhian Satria Yudha; Najaf, Abdul Rezha Efrat; Suryanto, Tri Lathif Mardi; Faroqi, Asif (Diponegoro University, 2024)
Implementation of ICT in various services in tertiary institutions needs to be accompanied by good quality. Therefore, it is necessary to evaluate to ensure the success of the service. The study aims to analyze the relationship between system quality, information quality and service quality to user satisfaction and then the relationship between user satisfaction to net benefit. In addition, three different system, namely academic information system, student portal and credit point system were evaluated to obtain broader understanding on those relationship. Survey data were collected from 451 students using those systems. SEM-PLS was applied to the obtained data. According to the empirical results, factors affected user satisfaction on academic information system was different than student portal and credit point system. However, it was found that user satisfaction affected net benefit. As a result, the successful factors on academic information system, student portal and credit point system were different. Thus, it was necessary to put a careful attention on the improvement aspect on each of those system. This paper aims to analyze factors affecting online services success to increase user satisfaction.